Improved GMP-compliant multi-dose production and quality control of 6-[18F]fluoro-L-DOPA - G. Luurtsema; H. H. Boersma; M. Schepers; A. M. T. de Vries; B. Maas; R. Zijlma; E. F. J. de Vries; P. H. Elsinga (SpringerOpen, 2016)
Abstract Background 6-[18F]Fluoro-L-3,4-dihydroxyphenylalanine (FDOPA) is a frequently used radiopharmaceutical for detecting neuroendocrine and brain tumors and for the differential diagnosis of Parkinson's disease. To meet the demand for FDOPA, a high-yield GMP-compliant production method is required. Therefore, this study aimed to improve the FDOPA production and quality control procedures to enable distribution of the radiopharmaceutical over distances. FDOPA was prepared by electrophilic fluorination of the trimethylstannyl precursor with [18F]F2, produced from [18O]2 via the double-shoot approach, leading to FDOPA with higher specific activity as compared to FDOPA which was synthesized, using [18F]F2 produced from 20Ne, leading to FDOPA with a lower specific activity. The quality control of the product was performed using a validated UPLC system and compared with quality control with a conventional HPLC system. Impurities were identified using UPLC-MS. Results The [18O]2 double-shoot radionuclide production method yielded significantly more [18F]F2 with less carrier F2 than the conventional method starting from 20Ne. After adjustment of radiolabeling parameters substantially higher amounts of FDOPA with higher specific activity could be obtained. Quality control by UPLC was much faster and detected more side-products than HPLC. UPLC-MS showed that the most important side-product was FDOPA-quinone, rather than 6-hydroxydopa as suggested by the European Pharmacopoeia. Conclusion The production and quality control of FDOPA were significantly improved by introducing the [18O]2 double-shoot radionuclide production method, and product analysis by UPLC, respectively. As a result, FDOPA is now routinely available for clinical practice and for distribution over distances.